Inventory management and its relationship with production planning in a textile company. (LACCEI, 2024)
The present research work is of a correlational – transversal type, quantitative approach, and non-experimental design, in which the poor production planning in a textile company in San Juan de Lurigancho was identified as a problem. In this regard, the following problem was formulated: To what extent is inventory management and production planning related in a textile company? On the other hand, in order to analyze the relationship between the variables inventory management and production planning, 2 questionnaires were developed and applied the same ones that were used with 34 collaborators of the company in analysis, in the questionnaire were raised 16 questions, whose distribution was the following: 8 items for the variable inventory management and 8 for production planning, using the Likert Scale. To determine the validity and reliability of the data collection instrument, these were subjected to reliability analysis by Cronbach's alpha coefficient and the results obtained were 67 percent for the inventory management questionnaire and 66 percent for the production planning questionnaire, so it is determined that the instruments are very reliable. Finally, the data were analyzed using statistics and the results were transferred to tables and figures, where the hypotheses were tested with Rho Spearman's statistical test allowing us to conclude that there is a significant relationship between the variables inventory management and production planning of 0.82.